Pendampingan Literasi Baca Tulis Berbasis Cerita Bergambar di Sekolah Dasar Negeri 066650 - Yani, Fitri; Lova, Stelly Martha; Lestari, Wiwik (Jurnal Pengabdian Pada Masyarakat METHABDI, 2024)
This service program aims: (1) To provide teachers with an understanding of strengthening reading and writing literacy through picture story-based wall magazines. (2) To implement strengthening reading and writing literacy through picture story-based wall magazines in elementary schools. Solutions to overcome partners' problems include: (1) Carrying out outreach to teachers about reading and writing literacy through the development of picture story-based media (2) Teachers are asked to observe and listen to reading and writing literacy activities through the development of picture story-based media (3) Holding discussion sessions and brainstorming with teachers about what they observe regarding reading and writing literacy activities through developing picture story-based media, and (4) Providing motivation to teachers about the importance of reading and writing literacy activities through developing picture story-based media for elementary school students. The method for implementing activities is carried out through 4 stages, including: (1) Preparation, (2) Implementation, (3) Monitoring and Evaluation, (4) Follow-up. The results of the service program that has been implemented are as follows: (1) The overall success category for teacher understanding is classified as good, meaning that the content of the material as a whole can be understood well by the teacher, so through this PkM activity, literacy is strengthened through the development of illustrated story-based media in elementary schools. It is believed that teachers can teach it well to students in elementary schools. (2) The mechanism of the activity, namely strengthening literacy through the development of picture-based media in elementary schools, can be concluded that the teachers of SDN Number 066650 can teach all subjects wisely using the development of picture-story-based media. In this way, teachers at SDN Number 066650 have broadly been able to actualize strengthening reading and writing literacy through picture story-based wall magazines at SDN Number 066650.